STRONGYLOIDES - Widyaningsih, Indah (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2009)
Strongyloidiasis is a parasitic disease caused by the roundworm Strongyloides stercoralis. The roundworm is found in soil contaminated by feces containing the worm, which then burrow through the skin and enter the bloodstream. They then enter the lungs and burrow through the tissue separating the airways from the esophafus and enter the digestive tract, where they lay eggs and reproduce. Many people who are infected with the roundworm have no symptoms of the disease. Strongyloides infections are more common in tropical and subtropical climates than in cooler temperate areas. Strongyloides stercoralis is a parasite that has both free-living and parasitic life cycles. In the parasitic life cycle, female worms are found in the superficial tissues of the human small intestine. There are no parasitic males.